Optimization of Oxidation Pond Efficiency in Animal Farm Wastewater Treatment - Ling, Teck Yee; Liew, C.F.; Modingin, A. (Universiti Sains Malaysia Press, 2007)
In this study, the decay rate of Escherichia coli (E. coli) in three different tropical soils from Sarawak, namely, peat soil, clay loam and silt loam was examined in the laboratory under constant temperature and saturated condition for a duration of 14 days. Results of this study indicated that the mean decay rate of E. coli ranged from 0.02 d-l in the clay loam to 0.14 d-l in the peat soil. The low decay rate in clay loam could be due to the higher quantity of clay particles in clay loam soil when compared to silt loam. This study also showed that E. coli population remained stable for three days in peat soil, six days in silt loam and as long as ten days in clay loam. Even though peat soil has higher organic matter, the decay rate was higher than that of clay loam. This is possibly due to the high acidity of the peat soil. This study indicated that the modified version of the linear flrst-order decay model which accounted for lag period is an appropriate model in the prediction of E. coli decay in all the three soils for the duration studied. Furthermore, there is an indication that the potential of E. coli pollution in tropical countries is higher than in temperate countries due to the higher survival rate. Therefore,proper management practice in the application and the disposal of animal waste should be formulated and implemented.